CAR-T CELL THERAPY: BIOTECHNOLOGICAL INNOVATION IN THE FIGHT AGAINST CANCER (CIPEEX, 2025)
Introduction: Cell therapy with T lymphocytes modified with chimeric antigen receptors (CAR-T) represents a biotechnological and therapeutic advance against cancer, especially in cases refractory to conventional treatments. Initially developed in the United States in the early 2010s, the technique arrived in Brazil through the Cell Therapy Center at the Ribeirão Preto School of Medicine, University of São Paulo (USP). Although promising, the therapy is still little known among academics and health professionals, which reinforces the importance of its dissemination in scientific and educational circles. Objective: The objective of this study was to present, in a didactic manner, the fundamentals of CAR-T cell therapy, highlighting its development, clinical application, observed results, and prospects for access in Brazil, contributing to a greater understanding of the topic among academics and health professionals. Methodology: The research was conducted by consulting journals available in the Google Scholar, PubMed, LILACS, and Virtual Health Library (VHL) databases. The study focused on systematizing information about the CAR-T cell production process, the main types of cancer in which the technique has been applied, and the advances recorded in Brazil, especially from initiatives by USP, the Ribeirão Preto Blood Center, and the Butantan Institute. Results: The therapy consists of collecting blood from the patient, isolating T cells, and sending them to specialized centers for genetic modification with a lentiviral vector. This vector, which is incapable of causing disease, inserts the CD19 receptor into lymphocytes, enabling them to recognize and attack cancer cells. After about 60 days, the modified cells are returned to the patient in a single dose, intravenously, promoting an effective immune response. Clinical studies have shown high remission rates in acute lymphoid leukemia and lymphomas, including in terminally ill patients. In Brazil, the first volunteer treated with the experimental technology achieved complete remission from advanced lymphoma. Other patients treated showed equally significant results. However, the cost of the procedure, around US$500,000 per patient, is a major barrier to its widespread use. Conclusion: CAR-T cell therapy is one of the most innovative strategies in the fight against cancer, offering new possibilities for patients without therapeutic alternatives. The success of the first Brazilian experiments reinforces the potential for incorporating the technique into the Unified Health System, provided that challenges related to infrastructure, costs, and regulation are overcome. The dissemination of this knowledge among academics and health professionals is essential to broaden the debate and promote public policies that enable access to cutting-edge treatments.
Keywords: Gene Therapy; Leukemia; Immuno-oncology; Molecular Biology